Organizational Culture in Change : Analyzing the Current State of Organizational Culture amid Changing Environment - Lahtinen, Nora Maria Nicola (My University, 2023)
The Covid-19 pandemic has had a significant impact on working methods, but also on people's thinking. Many have stopped to think about their values, and flexibility and meaningfulness are increasingly sought from work. When companies compete for talent, the organizational culture can serve as a competitive advantage for the company, which allows it to both stand out from its competitors and also create a meaningful workplace for its employees. The concept of organizational culture has not reached a consensus and the scope of the topic presents a challenge for research. In this study, the broad topic of organizational culture was delimited by focusing on the current state of the case company's organizational culture by utilizing Edgar H. Schein's (1985) organizational culture model, which divides organizational culture into three different levels, artifacts, beliefs and values, and deep basic assumptions. The study aims to find out the current state of organizational culture and how organizational culture is perceived after the changes caused by the Covid-19 pandemic. Schein's (1985) organizational culture model is used to assess the current state of organizational culture, and in addition the study aims to identify what kind of organizational culture the employees would like to pursue and what are the most significant development proposals for the development of the current organizational culture of the case company. The theoretical framework of the study focuses on organizational culture and leadership. The study followed a qualitative research approach and theme interviews were chosen as the research method. The themes of the interviews were based on Schein's (1985) organizational culture model and leadership. The results were analyzed using theory-based content analysis. In addition to the three levels of Schein's (1985) organizational culture model, the results were further structured into leadership and target organizational culture. Based on the results of the study, it can be stated that the employees' experience of the current state of the organizational culture, especially in terms of artifacts, beliefs and values and deep basic assumptions, is positive. In the descriptions of the target organizational culture, the importance of people, trust and leadership emerged. Leadership and showing appreciation were especially emphasized in the organizational culture development proposals. In addition, more presence, authenticity and consistency were expected from the leadership. The results showed the importance of leadership to organizational culture, which is in line with the findings in the literature. The results are also supported by other research results that the leadership is currently expected to be more humane. It can also be concluded that the utilization of Schein's (1985) organizational culture model is still relevant, and it offers an opportunity to interpret and clarify the broad topic of organizational culture.

Covid-19 pandemia on vaikuttanut merkittävästi työnteon tapoihin, mutta myös ihmisten ajatteluun. Monet ovat pysähtymään miettimään omia arvojaan ja työltä haetaan yhä enemmissä määrin joustavuutta ja ennen kaikkea merkityksellisyyttä. Yritysten kilpaillessa osaajista, organisaatiokulttuuri voi toimia yritykselle kilpailuetuna, jonka avulla se voi sekä erottua kilpailijoistaan että luoda työntekijöilleen merkityksellisen työpaikan. Organisaatiokulttuurin käsite ei ole saavuttanut yksimielisyyttä ja aiheen laajuus tarjoaa haasteen tutkimukselle. Tässä tutkimuksessa organisaatiokulttuurin aihetta pyritään rajaamaan keskittymällä case-yrityksen organisaatiokulttuurin nykytilaan hyödyntämällä Edgar H. Scheinin (1985) organisaatiokulttuurimallia, joka jakaa organisaatiokulttuurin kolmeen eri tasoon, artefakteihin, uskomuksiin ja arvoihin sekä syviin perusoletuksiin. Tutkimuksen tavoitteena on selvittää organisaatiokulttuurin nykytila ja miten organisaatiokulttuuri koetaan Covid-19 pandemian aiheuttamien muutosten jälkeen. Organisaatiokulttuurin nykytilan tarkasteluun hyödynnetään Scheinin (1985) organisaatiokulttuurimallia ja tämän lisäksi pyritään tunnistamaan, miten työntekijät kuvailevat tavoiteorganisaatiokulttuuria ja miten he kehittäisivät nykyistä organisaatiokulttuuria. Tutkimuksen teoreettinen viitekehys keskittyy organisaatiokulttuuriin ja johtajuuteen. Tutkimus noudatti laadullista tutkimusotetta ja tutkimusmenetelmäksi valittiin teemahaastattelut. Haastatteluiden teemat pohjautuivat Scheinin (1985) organisaatiokulttuurimalliin sekä johtamiseen. Tutkimusaineiston tulokset analysoitiin hyödyntämällä teorialähtöistä sisällönanalyysia. Tulokset jäsenneltiin edelleen Scheinin (1985) organisaatiokulttuurimallin kolmen tason lisäksi johtajuuteen ja tavoiteorganisaatiokulttuuriin. Tutkimuksen tulosten perusteella voidaan todeta, että työntekijöiden kokemus organisaatiokulttuurin nykytilasta erityisesti artefaktien, uskomusten ja arvojen sekä syvien perusoletusten osalta on myönteinen. Tavoiteorganisaatiokulttuurin kuvailuissa nousi esiin ihmisten, luottamuksen ja johtajuuden merkitys. Organisaatiokulttuurin kehitysehdotuksissa korostui erityisesti johtajuus ja arvostuksen osoittaminen. Johtajuudelta toivottiin enemmän läsnäoloa, aitoutta ja johdonmukaisuutta. Tulokset osoittivat johtajuuden merkityksen organisaatiokulttuuriin, joka on linjassa kirjallisuuden havaintoihin. Tuloksia tukevat myös muut tutkimustulokset siitä, että johtajuudelta toivotaan tällä hetkellä yhä enemmän inhimillisyyttä. On myös pääteltävissä, että Scheinin (1985) organisaatiokulttuurimallin hyödyntäminen on edelleen ajankohtainen, ja se tarjoaa mahdollisuuden tulkita ja selkeyttää organisaatiokulttuurin laajaa aihetta.
Keywords: organisational culture; culture; COVID-19; leadership (activity); fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Liiketoiminnan kehittämisen maisteriohjelma|en=Master´s Programme in Business Development|